Associations of lead biomarkers and delta-aminolevulinic acid dehydratase and vitamin D receptor genotypes with hematopoietic outcomes in Korean lead workers - Lee, Sung-Soo; Lee, Byung-Kook; Lee, Gag-Soo; Stewart, Walter F.; Simon, David; Kelsey, Karl; Todd, Andrew C.; Schwartz, Brian S. (Scandinavian Journal of Work, Environment & Health, 2001)
' ' OBJECTIVES ': 'This study compares and contrasts associations of dimercaptosuccinic acid (DMSA)-chelatable lead, tibia lead, and blood lead with five hematopoietic outcomes and evaluates the effect modification of these relations by polymorphisms in the delta-aminolevulinic acid dehydratase (ALAD) and vitamin D receptor (VDR) genes. ' ' METHODS ': 'A cross-sectional study of 798 lead workers and 135 unexposed referents was performed. ' ' RESULTS ': 'The DMSA-chelatable lead, tibia lead, and blood lead levels ranged in the lead (Pb) workers from 4.8 to 2103 g, -7 to 338 g Pb/g bone mineral, and 4 to 86 g/dl, respectively. The mean of the hemoglobin, hematocrit, zinc protoporphyrin (ZPP), and urinary (ALAU) and plasma (ALAP) delta-aminolevulinic acid levels of the lead workers were 14.2 (SD 1.4) g/dl, 42.4 (SD 4.4)%, 80.2 (SD 63.5) g/dl, 2.1 (SD 3.7) mg/l, and 17.7 (20.6) g/ml, respectively. After adjustment for the covariates, tibia lead was associated with all five hematopoietic outcomes, while blood lead and DMSA-chelatable lead were associated only with ZPP, ALAP, and ALAU. A comparison of the regression coefficients, total model adjusted R2 values, and delta R2 values revealed that blood lead was the best predictor of ZPP, ALAP, and ALAU. Only tibia lead was significantly associated with hemoglobin and hematocrit levels, but the additional variance explained by tibia lead was (≤1%). No clear effect modification of the relations between the lead biomarkers and hematopoietic outcomes studied was caused by ALAD or VDR genotype. ' ' CONCLUSIONS ': 'Lead must have a chronic, cumulative effect on hemoglobin and hematocrit levels, and any speculated mechanism cannot merely involve short-term plasma or target organ lead levels.
Keywords: bone lead; chelatable lead; cross-sectional study; delta-aminolevulinic acid dehydratase; dimercaptosuccinic acid; genetic polymorphisms; hematopoietic outcome; hematopoietic system; Korea; lead biomarker; lead worker; vitamin D receptor genotype